First Succinylome Profiling of Vibrio alginolyticus Reveals Key Role of Lysine Succinylation in Cellular Metabolism and Virulence - Zeng, Fuyuan; Pang, Huanying; Chen, Ying; Zheng, Hongwei; Li, Wanxin; Ramanathan, Srinivasan; Hoare, Rowena; Monaghan, Sean J.; Lin, Xiangmin; Jian, Jichang (Frontiers in Cellular and Infection Microbiology, 2021)
Recent studies have shown that a key strategy of many pathogens is to use post-translational modification (PTMs) to modulate host factors critical for infection. Lysine succinylation (Ksuc) is a major PTM widespread in prokaryotic and eukaryotic cells, and is associated with the regulation of numerous important cellular processes. Vibrio alginolyticus is a common pathogen that causes serious disease problems in aquaculture. Here we used the affinity enrichment method with LC-MS/MS to report the first identification of 2082 lysine succinylation sites on 671 proteins in V. alginolyticus, and compared this with the lysine acetylation of V. alginolyticus in our previous work. The Ksuc modification of SodB and PEPCK proteins were further validated by Co-immunoprecipitation combined with Western blotting. Bioinformatics analysis showed that the identified lysine succinylated proteins are involved in various biological processes and central metabolism pathways. Moreover, a total of 1,005 (25.4%) succinyl sites on 502 (37.3%) proteins were also found to be acetylated, which indicated that an extensive crosstalk between acetylation and succinylation in V. alginolyticus occurs, especially in three central metabolic pathways: glycolysis/gluconeogenesis, TCA cycle, and pyruvate metabolism. Furthermore, we found at least 50 (7.45%) succinylated virulence factors, including LuxS, Tdh, SodB, PEPCK, ClpP, and the Sec system to play an important role in bacterial virulence. Taken together, this systematic analysis provides a basis for further study on the pathophysiological role of lysine succinylation in V. alginolyticus and provides targets for the development of attenuated vaccines.